A conciliação entre história e saber absoluto na primeira concepção hegeliana de filosofia: em torno da articulação dos conceitos ‘pressuposto,’ ‘introdução’ e ‘carecimento da filosofia.’ - Crissiuma, Ricardo (Revista Eletrônica Estudos Hegelianos, 2017)
ABSTRACT: The present paper approaches the difficulties stemming from the double claim of Hegelian philosophy – to be absolute and “son” of its time – starting from a reconstitution of the articulation among the concepts of ‘presupposition,’ ‘need for philosophy’ and ‘introduction to philosophy’ in his first Jena writings. Instead of allotting such claims in different phases of Hegelian thought – abusing from the distinction between “young” and “mature” Hegel –, this article intends to focus on Hegel’s effort to simultaneously accommodate them starting from the assumption of two viewpoints: the viewpoint of philosophy and the viewpoint of doing philosophy. It is by stating this double claim and this double viewpoint that the meaning of Phenomenology of Spirit as an introduction to philosophy can be rescued without running the risk of being jeopardized by the two following alternatives: the introduction through philosophical criticism and the introduction through speculative logic.